Variations in the atlantoaxial joint detected by computed tomography in control patients - Peltonen, Henna; Berghem, Ksenia; Ortiz, Rebekka.; Honkaniemi, Jari (Elsevier, 2026)
Introduction: Whiplash injuries can lead to prolonged, widespread symptoms known as whiplashassociated disorders (WAD), which are suggested to be caused by instability of the C1-C2 junction.
However, there is limited published data on the typical extent of rotations and transitions of facets in the C1-C2 region.
Methods: Here we conducted a study examining the rotation between the C1 and C2 vertebrae, the lateral atlantodental interval, and C1-C2 facet joint alignment in 100 patients with no prior neck trauma
or prolonged neck complaints using computed tomography.
Results: Rotations up to 11◦ between C1 and C2 were observed in 84 % of the patients. Dens asymmetry of up to 1.9 mm was observed in 81 % of the patients. The facets were misaligned up to 5 mm in 42 % of the patients. There was no statistically significant correlation between the rotation of C1 and asymmetry of dens. As expected, head rotation in the head support correlated to the rotation between C1 and C2
and C1-C2 rotation correlated to the misalignment of facets.
Conclusion: The results of this study show that in a population without neck symptoms, almost all patients (98 %) exhibit rotation between C1 and C2, dens asymmetry or facet misalignment.
Implications for practice: These radiological findings represent normal anatomical variations rather than imply craniocervical junction instability.